COMMUNITY EMPOWERMENT OF SENGONKEREP HAMLET GUNUNG KIDUL THROUGH TRAINING ON KUNIR ASEM CANDY AND SOAP PRODUCTION - Hidayat, Riskin; Hadi , Syamsul; Fadhilah, Muinah; Agus Setiawan, Eko; Ayu Larasati, Adelia; Chandra Putry, Nur Anita; Kirana Putri , Fuadhillah; Heru Pratama, Yhoga; Fauzi , Fitriya (EMPOWERING HUMANITY, 2024)
Community service activities in Sengonkerep Hamlet, Gunung Kidul, aim to improve residents' skills and economic independence through training in making tamarind candy and dish soap. The training involved a participatory approach, introducing ingredients, production practices, and mentoring. As a result, participants' level of understanding increased from 20% to 80%, and small business income rose from 20% to 75%. In addition, customer satisfaction with the products reached 85%, while participation and cooperation among community members increased to 80%. The program succeeded in improving technical skills and opened up new business opportunities based on local and environmentally friendly materials. For sustainability, further training and strengthening partnerships with various parties to support the marketing and innovation of local products are recommended